Copper-Catalyzed Ultrasonic-Promoted Coupling of Acetylene Analogs, Dialkyl azo dicarboxylate, and Benzazoles to Assemble Tricyclic Fused- Ring [1,2,3]triazolo[3,4-b][1,3]benzazole Analogs - Nematpour, Manijeh; Karimi, Nafiseh; Mahboubi-Rabbani, Mohammad (Letters in Organic Chemistry, 2022)
An unprecedented copper-catalyzed reaction of acetylene analogs with dialkyl azo dicarboxylate and benzazole analogs via a cross-coupling sequence was reported. A library of triazolobenzazole fused ring systems including [1,2,3] triazolo [3,4-b] [1,3] benzothiazole, [1,2,3] triazolo [3,4-b] [1,3] benzoxazole and [1,2,3] triazolo[3,4-b][1,3]benzimidazole structures were obtained in moderate to excellent yields under very mild reaction conditions. Structural confirmation of the final products became possible using different methods like spectroscopy and elemental analysis. The control experiments indicated C-H activation of acetylene by copper salts, followed by cycloaddition between a 2-(phenylethynyl)benzo[d]azol-3(2H)-yl anion and azo dicarboxylate as the key mechanistic feature. The broad substrate scope with simple and easily affordable starting materials, as well as mild reaction conditions are the noticeable attributes of this methodology, which provides facile access to the desired products.
Keywords: terminal alkyne